Effects of Ghrelin on Triglyceride Accumulation and Glucose Uptake in Primary Cultured Rat Myoblasts under Palmitic Acid-Induced High Fat Conditions - Lingling Han; Jia Li; Ying Chen; Wei Wang; Dan Zhang; Guoliang Liu (International Journal of Endocrinology)
This study aimed to study the effects of acylated ghrelin on glucose and triglyceride metabolism in rat myoblasts under palmitic acid- (PA-) induced high fat conditions. Rat myoblasts were treated with 0, 10−11, 10−9, or 10−7 M acylated ghrelin and 0.3 mM PA for 12 h. Triglyceride accumulation was determined by Oil-Red-O staining and the glycerol phosphate dehydrogenase-peroxidase enzymatic method, and glucose uptake was determined by isotope tracer. The glucose transporter 4 (GLUT4), AMP-activated protein kinase (AMPK), acetyl-CoA carboxylase (ACC), and uncoupling protein 3 (UCP3) were assessed by RT-PCR and western blot. Compared to 0.3 mM PA, ghrelin at 10−9 and 10−7 M reduced triglyceride content (5.855 ± 0.352 versus 5.030 ± 0.129 and 4.158 ± 0.254 mM, P<0.05) and prevented PA-induced reduction of glucose uptake (1.717 ± 0.264 versus 2.233 ± 0.333 and 2.333 ± 0.273 10−2 pmol/g/min, P<0.05). The relative protein expression of p-AMPKα/AMPKα, UCP3, and p-ACC under 0.3 mM PA was significantly reduced compared to controls (all P<0.05), but those in the 10−9 and 10−7 M ghrelin groups were significantly protected from 0.3 mM PA (all P<0.05). In conclusion, acylated ghrelin reduced PA-induced triglyceride accumulation and prevented the PA-induced decrease in glucose uptake in rat myoblasts. These effects may involve fatty acid oxidation.